SHOTTKI BARERLI METALL -YARIM ÓTKIZGISHLI DIODLARINIŃ KEŃISLIK ZARYAD OBLASTIN ANIQŃAW - Abdreymov A.A.; Turdımuratov A.S.; Хоjаmuratova J.R. (PEDAGOGS, 2024)
This article analyzes semiconductor diodes with metal contacts of the Schottky barrier. To create an ohmic contact, the Fermi level in the semiconductor and metal must be equal. Due to the redistribution of charges, the energy bands bend towards the original location of the Fermi level of metals and semiconductors, which creates a space charge region (SCR).